Analisis Pengaruh Fraud Triangle Terhadap Kecurangan Akademik (Academic Fraud ) Mahasiswa Akuntansi Universitas Udayana - Sihombing, Michael; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p07, 2020)
Academic fraud is dishonest behavior committed by individuals in an academic environment in order to obtain their own benefits. This research aims to examine fraud triangle (pressure, opportunity, and rationalization) on the academic fraud of accounting students at Udayana University. The number of samples is 228 people, with the method of puposive sampling, especially non-probability sampling. Data collection is done through google form. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that pressure, opportunity, and rationalization had a positive and significant effect on academic fraud. Keywords: Pressure; Opportunity; Rationalization; Academic Fraud.